CNG-diesel dual fuel engine: a review on emissions and alternative fuels - Al-Saadi, Abdulwahab A. Abdulrahman; Aris, Ishak (IEEE, 2015)
This review paper is focusing on the investigations and studies on emissions of applying the Compressed Natural Gas (CNG) in the CNG-Diesel engines. As well as, the paper is highlighting studies that involved in the search for alternative fuels to be used for less emissions and good performance vehicles. Moreover, illustrating the developments occurred in this field for the previous five years, from year 2010 to year 2015. And, as observed, many researches indicate that there is a significant decreasing in emissions in the existence CNG-Diesel and other alternative fuels when comparing with the conventional pure diesel heavy duty vehicles engines. Furthermore, there are some attempts of finding alternative fuels were discussed in this paper.